Determining suitable municipalities for establishing a fish processing plant in the southern part of Zamboanga del Sur province - Mochtar, Zainal Abidin (2007)
The main objective of this study was to identify the most suitable municipalities for establishing a fish processing plant in the southern part of Zamboanga del Sur (ZDS) province...
"October 2007."
Thesis (M.A. Urban & Regional Planning)--University of the Philippines Diliman.
Keywords: Fishery processing plants -- Philippines -- Zamboanga del Sur